Emotions in Group Sports: A Narrative Review From a Social Identity Perspective - Campo, Mickael; Mackie, Diane M.; Sanchez, Xavier (Frontiers in Psychology, 2019)
Recently, novel lines of research have developed to study the influence of identity processes in sport-related behaviours. Yet, whereas emotions in sport are the result of a complex psychosocial process, little attention has been paid to examining the mechanisms that underlie how group membership influences athletes’ emotional experiences. The present narrative review aims at complementing the comprehensive review produced by Rees et al. (2015) on social identity in sport by reporting specific work on identity-based emotions in sport. To that end, we firstly overview the different terminology currently used in the field of emotions in groups to clarify the distinct nature of emotions that result from an individual’s social identity. Secondly, we discuss key concepts of social identity to better understand the mechanisms underlying identity-based emotions. Thirdly, we address existing knowledge on identity-based emotions in sport. We close the present narrative review by suggesting future research perspectives based on existing meta-theories of social identity. Evidence from the social psychology literature is discussed alongside existing works from the sport literature to propose a crucial theoretical approach to better understand emotions in sport.